User Interfaces of Mobile Dress-up Games - Kantelus, Jasmiina (My University, 2021)
Dress-up games are a popular genre among younger girls. Despite the popularity, the technical side of dress-up games has not been extensively studied before. This thesis aims to fix that by introducing their user interfaces. As dress-up games are nowadays mostly on mobile, the thesis focuses on mobile dress-up games. The objective of this thesis is to give an extensive overview of the user interfaces of dress-up games by presenting their history and common qualities. Another objective is to test how the user interfaces affect the user experience. The qualities of the user interfaces of mobile dress-up games are studied by using a sample of 50 Android dressup games. The games are examined one by one with a set of predefined questions to help in the analysis. Commonly used user interface elements are also defined along with layouts that are found to be common in the games. With this method, two widely used user interface styles are found and several aspects of the user interfaces are analysed in detail. The user experience is tested by developing a game with three distinct user interfaces. A test group is gathered to test the game and answer to a questionnaire about their opinions on the different aspects of the user interfaces. The results are then presented and analysed. Due to a small test group, the results are not conclusive, but they do indicate some patterns in preferences. Most of the testers preferred a certain user interface, and the analysis reveals why that is.

Pukemispelit ovat suosittuja nuorten tyttöjen keskuudessa. Suosiosta huolimatta pukemispelien teknisestä puolesta ei ole aiemmin juuri tehty tieteellistä tutkimusta, joten tämä tutkielma pyrkii korjaamaan tilannetta paneutumalla pukemispelien käyttöliittymiin. Koska pukemispelit ovat nykyään laajalti siirtyneet mobiilialustoille, tämä tutkielma keskittyy niihin. Tutkielman tavoite on antaa kattava kuva pukemispelien käyttöliittymistä käymällä läpi niiden historia ja yleisimmät ominaisuudet. Toinen tavoite on selvittää, kuinka niiden käyttöliittymät vaikuttavat käyttökokemukseen. Tutkiakseni käyttöliittymien ominaisuuksia olen ottanut 50 pelin otoksen Googlen Play Storesta. Pelit käydään läpi yksitellen ennaltamääriteltyjen kysymysten avulla. Tämän lisäksi otetaan selvää millaisia ulkoasuja pukemispeleissä yleisesti on ja mitkä ovat niissä yleisimmin käytetyt käyttöliittymäelementit. Menetelmän avulla löytyi kaksi yleisesti käytettyä käyttöliittymätyyliä ja useita käyttöliittymille ominaisia piirteitä. Käyttökokemuksen testaamista varten kehitettiin peli kolmella eri käyttöliittymällä. Peliä testasi testijoukko, joka vastasi lopuksi kyselyyn, jossa kysyttiin heidän mielipiteitään pelin eri ominaisuuksista. Kyselyn tulokset ja niiden analyysi esitetään tutkielman lopussa. Koska testijoukko oli pieni, tulokset ovat korkeitaan suuntaa antavia. Vastauksien perusteella yksi käyttöliittymä nousi ylitse muiden, ja tarkempi analyysi paljastaa mistä tämä johtui.
Keywords: dress-up games,user interface,user experience